Relationship between adolescent athletes' values and behavior in sport and perceived coach's character development competency - Stupuris, T.; Sukys, S. Tilindiene, I. (Education. Physical training. Sport, 2013)
Research background and hypothesis. This study examined the relations between reported youth athletes` prosocial and antisocial behavior and personal and social factors in sport context and whether these variables accounted for age and sports experience differences in reported behaviors values in sport and perceptions of coach`s character development competency. The aim of the research was to determine age and sports experience differences in manifestation of youth athletes` values in sport, perceived coach`s character development competency and behaviors that occur in sport, and to examine interrelations between these variables. Research methods. The sample included 201 athletes recruited from Kaunas and Alytus sports schools. The participants completed the Youth Sport Value Questionnaire-2 (YSVQ-2 - Lee et al., 2008), the Prosocial and Antisocial Behavior in Sport Scale (PABSS - Kavussanu, Boardley, 2009), and adapted version of the Coaching Efficacy Scale (CES- Feltz et al., 1999). Research results. The positive correlation between values in sport, perceived coach`s character development competency and prosocial behavior of athletes were established. These values also had negative correlations with antisocial behavior whereas status values correlated negatively with prosocial behavior. Coach`s character development competency was perceived stronger by younger athletes (p < 0.05). Competence values were more important to these athletes compared to older ones (p < 0.05). Discussion and conclusions. Research revealed the importance of moral and competence values for adolescent athlete`s moral behavior in sport. Perceived character-development effectiveness positively correlated with athletes` prosocial behavior; however, it was unrelated to antisocial behavior. Thus, perceiving the coach as being effective in instilling an attitude of good moral character may lead to an increased frequency of desirable behaviors but does not appear to have any effect on antisocial conduct. It was found that athletes` prosocial acts were more frequent than antisocial ones, however, more experienced athletes displayed more frequent antisocial behavior to the teammates. These findings are consistent with the previous presumption that low frequency of engagement in antisocial behaviors does not necessarily mean that one frequently engages in prosocial action, or vice versa.